Implementasi Kinerja Operasional dan Kepuasan Pelanggan Terhadap Tingkat Penjualan : (Studi Kasus Konter Hp D’One Acc) - Muhammad Rifki Damanik; Sri Ramadhani (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This study aims to analyze the impact of operational performance implementation and customer satisfaction on sales levels, with a case study on the D'One Acc Cellphone Counter. Operational performance includes internal process efficiency, quality control, and technology use, while customer satisfaction includes product quality, service, and customer experience. This study uses a quantitative method with a survey approach to collect data from customers and employees of the D'One Acc Cellphone Counter. The results of the analysis showed that there was a significant positive relationship between operational performance and customer satisfaction levels. In addition, customer satisfaction has a positive effect on sales levels. Good operational performance improves the quality of products and services, which in turn increases customer satisfaction and drives higher sales. These findings underscore the importance of integrating effective operational strategies and focusing on customer satisfaction to achieve increased sales. This research provides insight for the management of D'One Acc Hp Counters in formulating better strategies to improve operational performance and customer satisfaction, as well as maximize sales potential.